WISATA KAMPOENG PENDEKAR MENEMBUS LORONG WAKTU DENGAN TEORI LINIERITAS LIMA DIMENSI - Darwanto, Agus; Apriliani, Fadillah Eka; Atiqah, Qori Jihan (Badan Perencanaan Pembangunan Penelitian dan Pengembangan Daerah Kabupaten Cilacap, 2023)
Various tourist destinations offer unforgettable experiences for their visitors. Kampoeng Pendekar Tourism offers a five-dimensional experience that invites visitors to the ancient kingdom era. This research aims to find out how the management strategy of Kampoeng Pendekar Tourism in attracting visitors by applying the theory of linear five dimensions. Data collection was carried out through observation, interviews, surveys, and documentation. Data analysis was conducted using descriptive analysis by performing reduction and interpretation. The results of the study explain the highly innovative breakthrough by the management of Kampoeng Pendekar Tourism, which is able to linearize tourism, entertainment, and shows that elevate traditional content that appears old-fashioned into a five-dimensional sensation according to the theory introduced by Gillian Crampton Smith and Kevin Silver by creating a display of the past era, such as traditional houses and huts; officers, tour guides, and traders are required to wear Javanese traditional clothing; even the tour guides wear clothing resembling ancient warrior attire. All the food sold is traditional cuisine that is nearly extinct. The use of kepeng currency is the strongest sensation that brings visitors back to the past era. In addition, there are traditional games, art performances, and cultural attractions.